Intralesional Infiltration with Triamcinolone for the Management of Giant Cell Central Granuloma - Oviedo Quirós DDS, OMFS, MSc, Jorge (2016)
The central giant cell granuloma is a benign lesion on the jaws, which etiology is not yet known exactly. It has preference for young adults and female gender populations; it has predilection for jaws. Among the treatment options there are the infiltration of various solutions, curettage and resection in-bloc; the latter indicated in aggressive cases.  This article presents an aggressive case of central giant cell granuloma treated; it was an 11 year-old-male patient treated with triamcinolone acetonide intralesional injections during 6 weeks followed by surgical enucleation; a 14 month follow up after the treatment was finished, with no recurrence signs.